2020
DOI: 10.1103/physrevb.102.085126
|View full text |Cite
|
Sign up to set email alerts
|

Topological Lifshitz transition of the intersurface Fermi-arc loop in NbIrTe4

Abstract: Surface arcs (SAs) or Fermi arcs connecting pairs of bulk Weyl points with opposite chiralities are the signatures of Weyl semimetals in angle-resolved photoemission spectroscopy (ARPES) studies. The nontrivial topology of the bulk band structure guarantees the existence of these exotic Fermi arcs with connectivity that is strongly dependent on the surface. It has been theoretically proposed and experimentally confirmed that Fermi arcs at opposite surfaces can complete an unusual closed cyclotron orbit called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…It has been revealed that the dispersion of surface state in electronic systems is sensitive to the surface decoration, even leading to Lifshitz transition of surface states in some topological semimetals 29 , 30 . Here, the dispersion of the photonic DSS can also be tuned significantly by a simple surface characteristic, as depicted in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It has been revealed that the dispersion of surface state in electronic systems is sensitive to the surface decoration, even leading to Lifshitz transition of surface states in some topological semimetals 29 , 30 . Here, the dispersion of the photonic DSS can also be tuned significantly by a simple surface characteristic, as depicted in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…For example, the length of the electrodes along the smooth boundary can reach 4 ÎŒm [66], whereas the Fermi wavelength of the WSM in our system is boundaries are smooth enough, then the transverse momentum k z is approximately conserved during scattering. The WSM with a pair of FAs is a crucial building block in our proposal, which has been reported in NbIrTe 4 [49,[61][62][63], WP 2 [71], MoTe 2 [72], and YbMnBi 2 [73]. The main reason for the choice of the current time-reversal (T )-symmetric model is that it is the minimal model which contains a pair of FAs.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…3(a). To simulate the FAs in real materials [49,[61][62][63], we have introduced an on-site potential V on the top layer of the WSM lattice to introduce surface dispersion that yields curved FAs [51,52].…”
Section: B Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the negative MR due to the chiral anomaly can even have the opposite sign as the inter-node scattering is taken into account simultaneously [24]. Besides the smooth deformation of the Fermi surface, topological Lifshitz transition of the Fermi surface is studied as well in various topological materials [25][26][27][28][29][30], which is driven by different methods such as the temperature. An interesting question that arises is whether both the smooth deformation and the abrupt Lifshitz transition of the Fermi surface can be implemented by imposing a magnetic field, such that the underlying physics can be manifested under the same framework of MR measurements.…”
Section: Introductionmentioning
confidence: 99%